Pengaruh Media Pembelajaran Audio Visual Terhadap Hasil Belajar Siswa SMK - Diana Langgeng Mustikawati; Fahmy Zuhda Bahtiar (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
At this time technology can no longer be avoided, various sectors can take advantage of it, including the education sector. The way that can be utilized is by using learning media during the learning process because it will create a comfortable, enjoyable and interesting atmosphere to obtain maximum results. The aim of this research is to explain and identify the influence of using audio-visual learning media on vocational school student learning outcomes. This research aims to determine the effect of audio-visual learning media on vocational school student learning outcomes. To get what is desired, a quantitative research approach is used with experimental types and a Quasi Experimental research design. Data is calculated using statistical calculations (SPSS). In this research, simple linear regression analysis and t test were used. Testing the hypothesis with the t test obtained a t count value of 10.733 it means t hitung > t table (10.733 > 1.699) and significance (0.000 < 0.05) so it can be concluded that there is an influence of Audio Visual Learning Media on Vocational School Student Learning Outcomes.